Wills Eye Hospital atlas of clinical ophthalmology review of clinical ophthalmology on CD - Montzka, Dan.; Wills Eye Hospital (Philadelphia, Pa.) (Philadelphia : Lippincott-Raven, 1996)
(Producer) Contains all the text and images from the text, The Wills Eye Hospital atlas of clinical ophthalmology, plus over 220 high-quality pathology images, and 39 video segments related to neuro-ophthalmology, pediatrics, pathology, and clinical optics
Koleksi Multimedia Perpustakaan Perubatan
Keywords: Eye Diseases -- atlases -- interactive multimedia; Eye Diseases -- interactive multimedia